Asian Pacific Society of Cardiology Consensus Recommendations on Dyslipidaemia - Natalie Koh; Brian A Ference; Stephen J Nicholls; Ann Marie Navar; Derek P Chew; Karam Kostner; Ben He; Hung Fat Tse; Jamshed Dalal; Anwar Santoso; Junya Ako; Hayato Tada; et al. (European Cardiology Review)
The prevalence of dyslipidaemia has been increasing in the Asia-Pacific region and this is attributed to dietary changes and decreasing physical activity. While there has been substantial progress in dyslipidaemia therapy, its management in the region is hindered by limitations in awareness, adherence and healthcare costs. The Asian Pacific Society of Cardiology (APSC) developed these consensus recommendations to address the need for a unified approach to managing dyslipidaemia. These recommendations are intended to guide general cardiologists and internists in the assessment and treatment of dyslipidaemia and are hoped to pave the way for improving screening, early diagnosis and treatment. The APSC expert panel reviewed and appraised the evidence using the Grading of Recommendations Assessment, Development, and Evaluation system. Consensus recommendations were developed, which were then put to an online vote. The resulting consensus recommendations tackle contemporary issues in the management of dyslipidaemia, familial hypercholesterolaemia and lipoprotein(a) in the Asia-Pacific region.